2014
DOI: 10.2340/16501977-1863
|View full text |Cite
|
Sign up to set email alerts
|

Spina bifida and sexuality

Abstract: Results: Fifty-one percent of subjects regarded their sexual life as a failure or dysfunctional. However, 45% reported being satisfied with their sexual life. Participants with partners were more satisfied with their sexual life than those without partners. Faecal, but not urinary, incontinence was associated with poorer sexual function and less satisfaction. Fortynine percent of subjects indicated that the sexual education they received at puberty was useful; however, 32% lacked knowledge about their sexual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
0
26
1
Order By: Relevance
“…5 Clean intermittent catheterization (CIC), the use of bladder-active medications (BAMs), and close urological follow-up can mitigate many of the potentially life-threatening complications of neurogenic bladder dysfunction, but patients' quality of life (QOL) is considerably affected by the lifelong burden of these interventions, the lack of control of their ability to empty their bladders, and by incontinence and sexual dysfunction. 4,5,9,10,13,15,21,25,[28][29][30] For more than 100 years, researchers and clinicians have pursued a myriad of surgical remedies to allow reinnervation of the urinary bladder, attempting a variety of nerve repair and transfer techniques in experimental animals and in humans. 11 While there has been great success in the clinical use of nerve transfer techniques to reinnervate peripheral nerves of the extremities, 3 there is no surgical nerve transfer or repair procedure that is widely used in patients with neurogenic bladder dysfunction.…”
mentioning
confidence: 99%
“…5 Clean intermittent catheterization (CIC), the use of bladder-active medications (BAMs), and close urological follow-up can mitigate many of the potentially life-threatening complications of neurogenic bladder dysfunction, but patients' quality of life (QOL) is considerably affected by the lifelong burden of these interventions, the lack of control of their ability to empty their bladders, and by incontinence and sexual dysfunction. 4,5,9,10,13,15,21,25,[28][29][30] For more than 100 years, researchers and clinicians have pursued a myriad of surgical remedies to allow reinnervation of the urinary bladder, attempting a variety of nerve repair and transfer techniques in experimental animals and in humans. 11 While there has been great success in the clinical use of nerve transfer techniques to reinnervate peripheral nerves of the extremities, 3 there is no surgical nerve transfer or repair procedure that is widely used in patients with neurogenic bladder dysfunction.…”
mentioning
confidence: 99%
“…One study showed that 51% of patients with myelomeningocele reported that sexual life was a failure. 15 To complicate the picture it was found that patients with spina bifida who had urinary incontinence were less likely to be sexually active than their peers. 16 …”
Section: Discussionmentioning
confidence: 99%
“…79 By contrast, Game et al found that UI was the major factor related to deceased sexual activity –decreased desire, arousal and receptivity – among women with myelomeningocele. 74 Even the experience of wearing pads was seen as a barrier to intimacy.…”
Section: Findings and Recommendationsmentioning
confidence: 94%
“…7476 Issues regarding privacy, relevant to many women with CGCs who may live with their parents until at least late adulthood, play a large role in women’s sexual experiences. 74, 7779 Research is needed to better understand the barriers to sexual participation in men and women with CGCs and to develop and validate interventions to overcome these barriers.…”
Section: Findings and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation